Surprisingly benign histopathology in a case of malignant looking ovary - Rachna Agarwal; Alpana Singh; AG Radhika; Garima Vats (Barpeta Obstetrics and Gynaecological Society, 2019)
Xanthogranuloma is a non-neoplastic presentation of chronic inflammation commonly seen in gallbladder, kidneys and rarely seen in genital organs. Herein, we report a case of xanthogranulomatous oophoritis in a 45 year female who presented with lower abdominal pain and backache. There was an ill defined mass around 14 weeks size of gravid uterus. USG and CECT scan of abdomen confirmed it to be enlarged multiloculated right ovary 7.2×6.5×6.5 cms with multiple enhancing thick septations. CA125, CA19-9 and LDH were raised. The mass was clinically and radiologically misdiagnosed as ovarian neoplasm. Staging laparatomy was done. Histopathological findings revealed characteristics features of xanthograulomatous oophoritis. Xanthogranulomatous oophoritis should be kept in mind while dealing with cases of ovarian tumors to prevent misdiagnosis of malignancy and to avoid radical surgeries.